If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sin(2x + -30) = cos(20 + -4x) Reorder the terms: ins(-30 + 2x) = cos(20 + -4x) (-30 * ins + 2x * ins) = cos(20 + -4x) (-30ins + 2insx) = cos(20 + -4x) -30ins + 2insx = (20 * cos + -4x * cos) -30ins + 2insx = (20cos + -4cosx) Solving -30ins + 2insx = 20cos + -4cosx Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Reorder the terms: -20cos + 4cosx + -30ins + 2insx = 20cos + -4cosx + -20cos + 4cosx Reorder the terms: -20cos + 4cosx + -30ins + 2insx = 20cos + -20cos + -4cosx + 4cosx Combine like terms: 20cos + -20cos = 0 -20cos + 4cosx + -30ins + 2insx = 0 + -4cosx + 4cosx -20cos + 4cosx + -30ins + 2insx = -4cosx + 4cosx Combine like terms: -4cosx + 4cosx = 0 -20cos + 4cosx + -30ins + 2insx = 0 Factor out the Greatest Common Factor (GCF), '2s'. 2s(-10co + 2cox + -15in + inx) = 0 Ignore the factor 2.Subproblem 1
Set the factor 's' equal to zero and attempt to solve: Simplifying s = 0 Solving s = 0 Move all terms containing i to the left, all other terms to the right. Add '-1s' to each side of the equation. s + -1s = 0 + -1s Remove the zero: 0 = -1s Simplifying 0 = -1s The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-10co + 2cox + -15in + inx)' equal to zero and attempt to solve: Simplifying -10co + 2cox + -15in + inx = 0 Solving -10co + 2cox + -15in + inx = 0 Move all terms containing i to the left, all other terms to the right. Add '10co' to each side of the equation. -10co + 2cox + -15in + 10co + inx = 0 + 10co Reorder the terms: -10co + 10co + 2cox + -15in + inx = 0 + 10co Combine like terms: -10co + 10co = 0 0 + 2cox + -15in + inx = 0 + 10co 2cox + -15in + inx = 0 + 10co Remove the zero: 2cox + -15in + inx = 10co Add '-2cox' to each side of the equation. 2cox + -15in + -2cox + inx = 10co + -2cox Reorder the terms: 2cox + -2cox + -15in + inx = 10co + -2cox Combine like terms: 2cox + -2cox = 0 0 + -15in + inx = 10co + -2cox -15in + inx = 10co + -2cox The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| x/0,5=100/10 | | 5(-4+13)+2= | | -9=-160-9(-79) | | -18-24=-6m+4 | | 27x^3-9x^2-6x=0 | | -9=-180-9(-79) | | 3x/2=36/6 | | 2x/3x-18=2 | | 9w*3x= | | 12x^3+31x^2+20x=0 | | 4X+3=3(X+2) | | .9=-160-9(-79) | | 4x=x-4 | | 1-(1x+2)3=0 | | tg(-x/3)=-v3 | | 1-x+2=0 | | 3b^2-4b+1=0 | | 1/2.(10x-6)=x+16 | | 4x-6+6=x-4 | | 4x+-2+9=19 | | -5w-2=12 | | 4x-2+9=29 | | x/2=36/6 | | 2t-3d+8d-3= | | 57u+57= | | x(9x+2)=6 | | 12y+9y^2-21=0 | | -88=-160-9(-8) | | 2cosx=0.8 | | 32-12a-2a^2=0 | | 2.5=4.1x-9.8 | | y=105+26(2) |